Diskriminasi Gender dalam Perspektif Feminisme Postkolonial pada Novel Nyai Gowok Karya Budi Sardjono - Edy Suprayitno; Heru Setiawan; Asep Sulistyo Budi; Dyah Ayu Kurniawati (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the forms of gender discrimination experienced by female characters in the novel Nyai Gowok by Budi Sardjono, examined through the lens of postcolonial feminism. The scope of the study covers the representation of subordination, marginalization, and silencing of women resulting from the collaboration between local patriarchal structures and the legacy of colonial hegemony. This research employs a qualitative approach using a descriptive-interpretive literary textual analysis method. The theoretical framework applied is postcolonial feminism, particularly Gayatri Chakravorty Spivak's concept of the subaltern and the notion of double colonization. The data are drawn from narrative excerpts, dialogues, and events in the novel that represent gender discrimination against the characters Nyai Lindri and Martinah. The findings show that gender discrimination operates through three mutually reinforcing mechanisms: (1) direct silencing, manifested in physical violence, sexual violence, and explicit customary regulations; (2) symbolic silencing, occurring through language, labeling, and traditions that internalize subordination; and (3) misrepresentation, which distorts women's identities into objects of masculine interest.